(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Stress is a common factor that can lead to various health issues, including depression and anxiety. Aged garlic extract (AGE) has been suggested to have potential therapeutic benefits, including antidepressant and anxiolyticlike effects. This study aimed to investigate the effects of AGE on depressive and anxiety-like behavior induced by chronic restraint stress in mice using both in vivo and in silico approaches. In vivo experiments involved subjecting mice to chronic restraint stress to induce depressive-like behavior. The mice were then treated with AGE, and their behavioral outcomes were assessed using the forced swim test and tail suspension test, open field test, and elevated maze plus. Additionally, an in silico analysis was conducted to explore the potential mechanisms of action of AGE compounds, focusing on their interactions with the monoanime oxidase-A (MAO-A) enzyme. The in vivo experiments demonstrated that the administration of aged garlic extract significantly ameliorated behavioral deficits in mice subjected to chronic restraint stress. Specifically, AGE treatment led to reduced (p<0.05) immobility time in the forced swim test, with AGE125-treated mice showing (91.12 ± 4.94) seconds and AGE250-treated mice (73.0 ± 7.25) seconds, compared to (119.25 ± 7.13) seconds for the CRS group. Similarly, in the tail suspension test, immobility time was reduced to AGE125 (69.25 ± 5.65)s and AGE 250 (55.0 ± 6.74)s compared with CRS group (102.75 ± 6.84)s, thereby demonstrating antidepressant-like effects. Additionally, AGE-treated mice exhibited increased time spent in the periphery of the open field arena and spent more time in the open arms of the elevated plus maze, suggesting improved exploratory and anxiety-related behaviors compared to other groups. Additionally, in silico investigation suggested that compounds found in AGE may antagonize the MAO-A enzyme. This study provides evidence supporting the potential of AGE as a therapeutic agent for stress-related depressive disorders. AGE’s ability to improve behavioral outcomes in stressed mice may be related to the modulation of neurotransmitter systems, reduction of oxidative stress, and anti-inflammatory effects of its compounds, including its potential interaction with the MAO-A enzyme. Further research is needed to fully elucidate the mechanisms of action and confirm the efficacy and safety of AGE in humans. Dhaka Univ. J. Pharm. Sci. 24(2): 157-176, 2025 (December)